Bael at a glance - Singh, A K; Singh, Sanjay; Janakiram, T (Indian Horticulture, 2019)
Hardy tree with versatile fruit rich in dietary fibre, health benefiting phytochemicals, antioxidants, minerals and vitamin (riboflavin). Gaining importance for its therapeutical and nutraceutical values in changing climatic scenario. It is highly suitable to grow under rainfed semi-arid conditions, and having huge genetic variability among the existing population. It is ideal fruit for health, nutritional and environmental security.